RETRACTED ARTICLE: Monitoring of operational conditions of fuel cells by using machine learning - Shrote, Andip Babanrao; Kumar, K Kiran; Kaur, Chamandeep; Al Ansari, Mohammed Saleh; Singh, Pallavi; Hazela, Bramah; G C, Madhu (EAI Endorsed Transactions on Internet of Things, 2024)
This article has been retracted at the request of our research integrity team. You can find the retraction notice at the following link https://doi.org/10.4108/eetiot.7176
Keywords: Testing data; Fuel cell; Performance; AIML